Landslide societal risk in Portugal in the period 1865-2015 - Pereira, Susana (2020)
The existence of reliable databases on natural disasters is crucial to study mortality due to natural hazards in terms of temporal trends, spatial distribution and epidemiological topics. Features on fatalities caused by different types of hazards can be found for instance in natural hazard databases (e.g. EM-DAT, DISASTER) based on documental sources, demographic statistics, death certificates from hospitals and civil protection authorities. There are some constraints in the inclusion criteria of mortality data in natural disasters databases. For instance, the EM-DAT only record natural disasters that have caused at least 10 fatalities, while the Portuguese DISASTER database includes every occurrence that caused fatalities regardless of their number. In Portugal, social impacts caused by landslides occurred in the period 1865-2015 are gathered in the DISASTER database. This database includes social consequences (fatalities, injuries, missing people, evacuated people and homeless people) caused by landslides referred in newspapers. The DISASTER database contains 289 damaging landslides that caused 238 fatalities. In the present work we explore the mortality patterns resulting from damaging landslides in the country for an extended period. In this work we aim to: (i) analyse the spatio-temporal analysis of damaging landslides occurred in the last 155 years; (ii) analyse the frequency and the temporal evolution of fatal landslides; (iii) analyse the spatio-temporal distribution of fatalities generated by landslides; (iii) identify the most deadly landside types; (iv) verify gender tendencies in mortality resulting from landslides; and (v) evaluate the individual and societal risk. Individual risk is evaluated computing mortality rates for landslides, which are calculated based on the annual average population and the annual average of fatalities. The societal risk is evaluated by plotting the annual frequency of landslide cases that generated fatalities (F-N curves). The results demonstrate the absence of any exponential growth in time of both landslide cases and landslide mortality in Portugal. The highest number of landslide cases and related mortalities occurred in the period of 1935-1969 in relation to very wet years. After this period, the number of landslide mortalities decreased, although fatalities remained higher than those registered in the period of 1865-1934. The landslide fatalities mainly occurred in the north of the Tagus valley where the geologic and geomorphologic conditions are more prone to landslides. The Lisbon area registered a mortality hotspot, which is explained by natural conditions combined with the high exposure of population to landslide risk. In the South of Portugal landslide fatalities are constrained to coastal cliffs reflecting a careless intensive use of the coastal areas for tourism. Falls and flows were responsible for the highest number of fatalities associated with landslides. Males were found to have the highest frequency of fatalities and fatalities inside buildings were dominant, mostly in rural areas. In conclusion, the spatial patterns of landslide mortality can be related to the unequal distribution of predisposing conditions to landslides, changes in the land use and exposure and social vulnerability to landslide hazards.